Estudio comparativo entre la leche materna y las fórmulas lácteas en el estado nutricional de los niños del Subcentro José Luis Tamayo, Salinas, Santa Elena. Noviembre 2023 - abril 2024. - Bustamante Chang, Darling Joan (2024)
Exclusive breastfeeding is considered the appropriate diet for the child, since it provides all the nutrients that the child needs in the early stages in a balanced way and at the same time protects him or her against diseases that may occur in the short or long term. Therefore, the objective of the research is to determine the relationship between breast milk and milk formulas in the nutritional status of the children of the José Luis Tamayo subcenter, in the Salinas Canton, Province of Santa Elena in the period from November 2023 to April 2023. 2024. The methodology was descriptive, quantitative and longitudinal, to determine the population sample, simple random sampling was used and the result was 115 children under 6 months. The results regarding children who consume breast milk present favorable differences in their nutritional status with the weight/age indicator, however the group of children who consume milk formulas with respect to size/age is not so affected. In conclusion, the nutritional status of children during the first six months of age is closely related to the type of diet received, with breast milk being the preferred option for optimal development, in addition to socioeconomic and cultural factors exerting a significant influence on Choosing between breast milk and formula milk, these factors may include availability of resources, education, cultural beliefs, and poor eating habits.